2019
DOI: 10.1101/641308
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

How thermophilic Gram-positive organisms perform extracellular electron transfer: characterization of the cell surface terminal reductase OcwA

Abstract: Extracellular electron transfer is the key process underpinning the development of bioelectrochemical systems for the production of energy or added-value compounds.Thermincola potens JR is a promising Gram-positive bacterium to be used in these systems because it is thermophilic. In this paper we describe the structural and functional properties of the nonaheme cytochrome OcwA, which is the terminal reductase of this organism. The structure of OcwA, determined at 2.2Å resolution shows that the overall-fold and… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 54 publications
0
11
0
Order By: Relevance
“…The putative extracellular electron transfer pathway was proposed to be composed of four proteins: a decaheme cytochrome (TherJR_1117 in T. potens and Tfer_0070 in T. ferriacetica ) that is anchored to the inner membrane and is proposed to receive electrons from the menaquinone pool; a periplasmic decaheme cytochrome (TherJR_0333 in T. potens and Tfer_1887 in T. ferriacetica ) proposed to transfer electrons within the periplasmic space of Thermincola ; a hexaheme cytochrome, proposed to be embedded in the peptidoglycan (TherJR_1122 in T. potens and Tfer_0075 in T. ferriacetica ), and a nonaheme cytochrome proposed to be the terminal reductase localized at the cell surface of the bacteria (TherJR_2595 in T. potens and Tfer_3197 in T. ferriacetica ) (Figure ). From these, only the cell‐surface multiheme cytochrome, named outer cell‐wall cytochrome A (OcwA) was characterized in detail …”
Section: The Cell‐surface Cytochromes Of Gram‐positive Bacteriamentioning
confidence: 99%
See 1 more Smart Citation
“…The putative extracellular electron transfer pathway was proposed to be composed of four proteins: a decaheme cytochrome (TherJR_1117 in T. potens and Tfer_0070 in T. ferriacetica ) that is anchored to the inner membrane and is proposed to receive electrons from the menaquinone pool; a periplasmic decaheme cytochrome (TherJR_0333 in T. potens and Tfer_1887 in T. ferriacetica ) proposed to transfer electrons within the periplasmic space of Thermincola ; a hexaheme cytochrome, proposed to be embedded in the peptidoglycan (TherJR_1122 in T. potens and Tfer_0075 in T. ferriacetica ), and a nonaheme cytochrome proposed to be the terminal reductase localized at the cell surface of the bacteria (TherJR_2595 in T. potens and Tfer_3197 in T. ferriacetica ) (Figure ). From these, only the cell‐surface multiheme cytochrome, named outer cell‐wall cytochrome A (OcwA) was characterized in detail …”
Section: The Cell‐surface Cytochromes Of Gram‐positive Bacteriamentioning
confidence: 99%
“…It contains five hemes with the typical bis‐histidine axial coordination (hemes 1, 3, 4, 6, 7, and 8), one heme with histidine‐methionine coordination (heme 9), and two hemes with a histidine as the proximal ligand and an open coordination side as the distal position (hemes 2 and 5). It was shown that these two high‐spin hemes, located at opposite ends of the nine heme arrangement may work as the putative active sites for substrate binding, which is a novelty within the family of multiheme cytochromes …”
Section: The Cell‐surface Cytochromes Of Gram‐positive Bacteriamentioning
confidence: 99%
“…Like Gram-negative bacteria, some Gram-positive bacteria rely on MHC to transfer electrons to solid electron acceptors outside of the cell. Up to date the only cell-surface cytochrome from Gram-positive bacteria that have been characterized in detailed was the OcwA from T. potens , showing that it can reduce solid electron acceptors, soluble electron shuttles and oxyanions [27] . Nevertheless, the way this protein is anchored and arranged at the cell surface and how electrons are transferred across the cell wall are still to be determined.…”
Section: Discussionmentioning
confidence: 99%
“…is composed by an inner-membrane MHC that receive electrons from the menaquinone pool, that then transfers the electrons to a periplasmic cytochrome. The transfer of electrons outside of the cell depends on a hexaheme cytochrome that was proposed to be embedded in the peptidoglycan at the cell wall and on the nine-heme cytochrome OcwA present at the cell-surface of these bacteria, responsible to reduce solid electron acceptors, electron shuttles and oxyanions [27] , [29] ( Fig. 2 B).…”
Section: Direct Electron Transfer In Gram-positive Bacteriamentioning
confidence: 99%
See 1 more Smart Citation